Model Formulation for Estimating Oil Extraction Rate to Measure Oil Extraction Efficiency in Palm Oil Mill - M Hudori; Iskandar, Isdaryanto; Setyanto, Djoko (TALENTA Publisher, 2023)
FFB that has high HQE and FCI will determine the OER that will be obtained at POM, so that OER can be estimated using HQE and FCI, ie by calculating the oil content in FFB and the potential for oil loss in loose fruit that is not collected in the plantation area. The purpose of this study was to formulate an OER estimation model to determine the processing efficiency of POM. This research is a qualitative and quantitative analysis research, which is a scientific study to formulate an OER estimation model based on HQE and FCI parameters which will be used as the dependent variable. Based on the results and discussion it can be concluded that OER, which is a parameter of oil palm processing performance at POM, can be estimated using a model formulation developed from HQE and FCI variables, where these variables are indicators of FFB harvesting performance in oil palm plantations.